Sustainable Growth of Central Asian Countries: Opportunities and Prospects - L. Sh. Sultanova (Экономика: стратегия и практика, 2025)
The purpose of the article is to examine the main socio-economic trends in Central Asian countries and to identify prospects and opportunities for achieving sustainable growth goals. The study hypothesizes that the region has the potential for sustainable growth and strengthening its geopolitical position based on the synergy of strengths, strengthening weaknesses, and creating new opportunities. This study uses the methods of structural and logical analysis, descriptive statistics, factor analysis, predictive expert assessments, SWOT analysis of the economies of Uzbekistan and Kazakhstan, and comparative analysis of investment attractiveness. A comparative analysis of Central Asian countries was conducted at the level of individual countries, the region as a whole, and in comparison, with global averages. Key indicators used included gross domestic product (GDP), GDP per capita, GDP growth rate, unemployment rate, average salary, demographic indicators, expenditures on education, the enrollment rate in higher education, unit costs of research and development, and the human capital index. The results show that in order to strengthen their positions, the Central Asian countries must: ensure a balanced approach to economic and social development in accordance with the Sustainable Development Goals; focus government and business efforts on job creation; ensure the diversification of the national economy for a gradual transition from traditional industries to industries with higher added value. Further research requires expanding the analysis of the development of the industrial and service sectors to understand how transit potential affects the development of the economic structure; it is necessary to use econometric modeling and analysis methods.